ISLAM, TEKNOLOGI, DAN ARTIFICIAL INTELLIGENCE TANTANGAN EPISTEMOLOGI, ETIKA DIGITAL, DAN OTORITAS KEAGAMAAN DALAM KONTEKS PENDIDIKAN ISLAM - Andika Apriansyah; Uswatun Hasanah; Muhammad Fauzi; Nyimas Umi Kalsum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the relationship between Islam, technology, and artificial intelligence through four main focuses: digital religion; the dynamics of fatwas and religious authority in the AI ​​era; the ethics of technology from an Islamic perspective; and the emerging epistemological challenges in education. This method includes a literature review and thematic content analysis of various relevant scientific sources. The results of the study indicate that traditional religious authority has been transformed by the presence of AI in Islamic education, particularly due to the emergence of digital platforms that allow fatwas to be distributed more widely and are no longer centralized. From an ethical perspective, the principle of maqasid al-shariah can be an important foundation for assessing and directing the development of artificial intelligence technology to remain aligned with Islamic values. From an epistemological perspective, however, artificial intelligence presents new challenges to the concept of knowledge in Islam, particularly related to the distinction between certain knowledge (ilm al-yaqin) and conjectural knowledge (zanniyyat). Based on the results, this study emphasizes the importance of building an artificial intelligence literacy curriculum in Islamic educational institutions that is based on the values ​​of the Qur'an and the prophetic tradition.